Nodo de oportunidades para mujeres y niños víctimas de la violencia (2021)
The node of opportunities for women and children victims of violence arises with the studies for the design of the master plan for the exploration route of the Llanera and the partial plan for the Sicuani eco-cultural centrality, of which one of the main problems is high rates of inequality, discrimination, Lack of educational and economic opportunities presented by the most vulnerable population groups, in this case children, women and mothers head of the household, presenting cases between intra-family violence, sexual assault and homicides, with Casanare being the department with the highest data. A pattern of support centers is studied and identified, finding spaces lacking natural light, without any dynamism in their interior, generating stress and emotional blockage in the user, making their recovery longer, starting from this as an architectural problem, light is proposed as sensory activation element through healing architecture focused on a sustainable approach where materiality and spatial comfort are taken into account.